2015
DOI: 10.5194/piahs-369-19-2015
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation delivery trajectories associated with extreme river flow for the Waitaki River, New Zealand

Abstract: Abstract. Analysis of large-scale climate conditions associated with extreme river flow is an important first step in the development of predictive relationships for such events. The potential of this approach is demonstrated here for the Waitaki River (a river of national importance in terms of electricity generation), in the Southern Alps of New Zealand. Here, atmospheric circulation anomalies and air parcel trajectories associated with such events are investigated for the period 1960-2010, using the NCEP/NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…Indeed, northwesterly airflow under this situation is associated often with high precipitation over the Southern Alps (e.g. Pearson and Henderson, 2004;Salinger and Mullan, 1999) and furthermore to high upper Waitaki lake inflow at both the monthly and event scale (Kingston et al, 2016;Kingston and McMecking, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, northwesterly airflow under this situation is associated often with high precipitation over the Southern Alps (e.g. Pearson and Henderson, 2004;Salinger and Mullan, 1999) and furthermore to high upper Waitaki lake inflow at both the monthly and event scale (Kingston et al, 2016;Kingston and McMecking, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our results also suggest that the available moisture in the subtropical regions east of Australia could be a key variable to include in future studies, especially for the northern parts of ANZ. The question of the moisture sources for ARs could be addressed for example, by using back trajectories or Lagrangian approaches-as already indicated by Kingston and McMecking (2015) for flooding events in the Southern Alps. Latent heat fluxes at the interface between atmosphere and oceans (e.g., over Tasman and Coral seas) or continent (Australia) are intuitive candidates that could favor increased moisture in the lower troposphere, more likely to lead to AR formations.…”
Section: Discussionmentioning
confidence: 99%
“…The back-wards trajectory thus reveals how parcels of air reach the hydrologically significant event and interact with larger-scale weather types and/or circulation patterns (e.g. Kingston and McMecking, 2015;Sahin et al, 2015). Alternatively to tracking the physical trajectory of air parcels, the geochemical characteristics of precipitation delivered to the land surface can also provide information on air-mass characteristics, precipitation source and moisture recycling from the surface to the atmosphere (e.g.…”
Section: Atmospheric Pathways To Precipitation Deliverymentioning
confidence: 99%
“…Seasonal lag-lead relationships typically focus on the role of slowly-varying components of the climate system, particularly SSTs (e.g. Kingston et al, 2013;Ionita et al, 2017), whereas on daily to weekly scales it has recently been shown that by focussing on water vapour transport instead of directly on precipitation has the potential to increase the forecast horizon by up to three days (Lavers et al, 2014).…”
Section: Hydrological Predictionmentioning
confidence: 99%